Combined Use of Systems Methodologies in Creative Managing the Problem Situations: Key Features, Benefits and Challenges (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Management problems in contemporary enterprises should be, according to their increasing complexity and diversity, observed and explored as the management problem situations, that is the systems of problems. Creative dealing with these complex, dynamic and ambiguous problem situations implied the development of a great variety of systems approaches to problem solving, i.e. systems methodologies for problem situations structuring. Since no methodology is able to explore all aspects of the complex problem situations in enterprises, the topic of the paper is combined use of systems methodologies in creative managing the problem situations. The goal of this paper is to highlight the key features, benefits and challenges of combining the systems methodologies in creative managing the problem situations in enterprises. Therefore, research in the paper is relied on Critical Systems Thinking as a conceptual framework for combined use of systems methodologies. Despite the limitations of combining the systems methodologies, methodologically appropriate combined use of systems methodologies enables improvement of managing the problem situations in contemporary enterprises.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.